Does Teaching Factory Matter for Vocational School Students? - Djoko Dwi Kusumojanto; Agustina Wulandari (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2020)
This research aims to understand the planning, implementation, relevance to student competency skills, as well as supporting and inhibiting factors of the teaching factory. This study involved a qualitative descriptive to gain a better understanding of the phenomenon and incorporated with observation technique, interviews, and documentation. The data in this research was divided into two: primary and secondary data. The primary data were collected from selected informants, and the secondary data was gathered from supporting documents in this research. The collected data further analyzed using the triangulation technique for validity and data reduction to provide a conclusion. The findings indicate that planning is realized by creating an organizational structure that manages the teaching factory. In addition, in planning students to practice in the teaching factory lab and carry out the tasks in the lab, for relevance to the competency skills in the classroom according to the existing basic competence which relevant to the existing practice in the teaching factory lab for the supporting factors, the facilities and infrastructure are already supportive. The human resources are adequate, and the inhibiting factor in terms of assistance from teachers in the lab is still lacking.   Keywords: Teaching factory, Online business, Marketing, Students' activities